The Spatiotemporal Regulation of cAMP Signaling in Blood Platelets—Old Friends and New Players - Raslan, Zaher; Aburima, Ahmed; Naseem, Khalid M. (Frontiers in Pharmacology, 2015)
Atherothrombosis, the pathology underlying numerous cardiovascular diseases, is a major cause of death globally. Hyperactive blood platelets play a key role in the atherothrombotic process through the release of inflammatory mediators and formation of thrombi. In healthy blood vessels, excessive platelet activation is restricted by endothelial-derived prostacyclin (PGI2) through cyclic adenosine-5’-monophosphate (cAMP) and protein kinase A (PKA)-dependent mechanisms. Elevation in intracellular cAMP is associated with the control of a number of distinct platelet functions including actin polymerisation, granule secretion, calcium mobilisation and integrin activation. Unfortunately, in atherosclerotic disease the protective effects of cAMP are compromised, which may contribute to pathological thrombosis. The cAMP signalling network in platelets is highly complex with the presence of multiple isoforms of adenylyl cyclase (AC), PKA and phosphodiesterases (PDE). However, a precise understanding of the relationship between specific AC, PKA and PDE isoforms, and how individual signalling substrates are targeted to control distinct platelet functions is still lacking. In other cells types, compartmentalisation of cAMP signalling has emerged as a key mechanism to allow precise control of specific cell functions. A-kinase anchoring proteins (AKAPs) play an important role in this spatiotemporal regulation of cAMP signalling networks. Evidence of AKAP-mediated compartmentalisation of cAMP signalling in blood platelets has begun to emerge and is providing new insights into the regulation of platelet function. Dissecting the mechanisms that allow cAMP to control excessive platelet activity without preventing effective haemostasis may unleash the possibility of therapeutic targeting of the pathway to control unwanted platelet activity.